2005
DOI: 10.1093/eurheartj/ehi100
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of treatment delay in patients with ST-elevation myocardial infarction: impact of pre-hospital diagnosis and direct referral to primary percutanous coronary intervention

Abstract: In a cohort of patients scheduled for admission to a local hospital and subsequent transferral to an interventional centre for primary PCI, those diagnosed pre-hospitally had shorter treatment delay compared with those diagnosed in hospital, both in the setting of initial admission to a local hospital, and to an even larger extent in the setting of referral directly to the interventional centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(98 citation statements)
references
References 39 publications
3
93
0
2
Order By: Relevance
“…The second study reported an 11% in-hospital mortality for STEMI patients brought by EMS without a prehospital ECG versus 5% in those with a prehospital ECG. 657 …”
Section: Consensus On Sciencementioning
confidence: 99%
See 3 more Smart Citations
“…The second study reported an 11% in-hospital mortality for STEMI patients brought by EMS without a prehospital ECG versus 5% in those with a prehospital ECG. 657 …”
Section: Consensus On Sciencementioning
confidence: 99%
“…Eight studies demonstrated a reduction in the reperfusion delay (with varied time interval definitions) ranging from 15 to 65 minutes in patients treated with PCI (LOE 2 [655][656][657][658] ; LOE 3 112,659,660 ; LOE 4 661 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Coronary artery disease provides an ideal target for telehealth intervention because of its great and increasing financial cost, and the overrepresentation of heart disease in rural and remote communities (Hooper et al, 2001). The major purpose of pre-hospital 12-lead ECG diagnosis is the early detection of acute myocardial infarction with ST-segment elevation and the communication of that information to the receiving emergency physician before the arrival of the patient (Terkelsen et al, 2005). Transmission of prehospital 12-lead ECG directly to the attending cardiologist's mobile telephone decreased door-to-device time by >1 hour when patients with ST-elevation myocardial infarction were transported directly to invasive centres, bypassing local hospitals (Sejersten et al, 2008).…”
Section: Telecardiologymentioning
confidence: 99%